Transforming type : new directions in kinetic typography - Brownie, Barbara (London ; New York : Bloomsbury, 2015)
"Transforming Type examines kinetic, or moving type, in a range of fields including film, television, typographic animation, and motion graphics, with examples including film and television title sequences, television idents, advertising, interactive poetry and experimental animation. Barbara Brownie addresses different kinds of kineticism and the issues that arise when type transforms itself, challenging the boundaries between type and image. She explores the extent to which existing typography theory can be applied to kinetic media, and attempts to provide a new typology of kinetic typography, enabling readers to define and describe contemporary practice"--
Includes bibliographical references (pages 103-110) and index.
Keywords: Graphic design (Typography); Kinetic art; Credit titles (Motion pictures, television, etc.); Logos (Symbols); DESIGN / General; DESIGN / Graphic Arts / General